Towards the development of a clinically effective interoperable epilepsy electronic patient record - Mc Quaid, Louise (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2016)
eHealth including Electronic Patient Records1(EPRs), is a key enabler to effectively support the coordinated approach to chronic disease management (CDM), including epilepsy, by improving information flow between patients and providers and among providers themselves. The potential for eHealth applications to reduce medical error, improve patient outcomes and reduce healthcare costs is recognised.(1) However, it has been proven that eHealth projects have failed to meet end-users requirements or are considered incomplete and not fit for purpose.(2) eHealth can benefit from employing a sociotechnical ethos that views the human, organisational and technical components of a system as a network that must be managed collectively in order to realise improved healthcare. Enabling interoperability, the ability to safely share and communicate information between eHealth applications across multiple healthcare providers regardless of geographical location, is also an important consideration for successful eHealth applications. This research, conducted using a qualitative case study, examines how a sociotechnical approach to EPR requirements, design and deployment can be used to meet clinical requirements. The findings suggest that an EPR based on an STS ethos results in a workable and usable system for end-users. This thesis also considers how existing EPRs can share and communicate information to support interoperability between eHealth applications. It provides a methodology, which was validated using a case study, for mapping from an existing relational EPR to the Health Level Seven (HL7) Clinical Documents Architecture Standard (CDA). It also found that it is possible to map from an existing relational EPR to the HL7 CDA standard to enable interoperability subject to certain constraints such as involving both clinical and technical expertise. This research has made a theoretical contribution to health informatics research and also has relevance to practice. Specifically, the study improved understanding in the area of design and deployment of EPRs using sociotechnical perspectives in a real world setting and contributes to the literature on healthcare interoperability standards.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin